Feelings and Consumer Decision Making: Extending the Appraisal‐Tendency Framework - Lerner, Jennifer S.; Han, Seunghee; Keltner, Dacher (Journal of Consumer Psychology, 2007)
The target article (Han, Lerner, & Keltner, 2007) presents the Appraisal‐Tendency Framework as a basis for predicting the influence of specific emotions on consumer decision making. The 3 thought‐provoking commentaries by Shiv (2007); Yates (2007); and Cavanaugh, Bettman, Luce, and Payne (2007) highlighted the need to (a) distinguish different types of emotional inputs; (b) specify constructs and mechanisms more concretely; and (c) extend the framework in new, creative ways. This response integrates the specific comments into overarching themes and addresses them.